Eosinophilic mastitis: A chameleon disease in rheumatologists' domain - Shruti Bajad; Rohit Bajaj; Dhaval Tanna; Muzaffar Bindroo; Kanchan Kaur; Rajiva Gupta (Indian Journal of Rheumatology)
We report a rare case of eosinophilic mastitis in a young asthmatic female who presented with a breast lump and was managed conservatively with a successful outcome. Eosinophilic mastitis, characterized by eosinophilic infiltration of mammary glands, is one such entity which is frequently given a miss, and is diagnosed based on histopathological analysis. The identification of this disease is a primary step in the management of such benign disorders which can be successfully treated conservatively avoiding any surgical intervention and morbidities thereafter. Because presentation can be similar and confusing enough, we took a cue from the history of asthma, urticaria, and peripheral eosinophilia to clinch the diagnosis of eosinophilic mastitis, which was further confirmed on biopsy. To the best of our knowledge, this happens to be the youngest female patient aged 27 years who also had urticaria along with other eosinophilic manifestations, which is unreported in other cases and makes our case exceptional. She was treated with glucocorticoids and antihistaminics and is presently symptom free.